At zero point : discourse, culture, and satire in Restoration England - Zimbardo, Rose A. (The University Press of Kentucky, 2015)
At Zero Point presents an entirely new way of looking at Restoration culture, discourse, and satire. The book locates a rupture in English culture and epistemology not at the end of the eighteenth century (when it occurred in France) but at the end of the seventeenth century. Rose Zimbardo's hypothesis is based on Hans Blumenberg's concept of ""zero point""--The moment when an epistemology collapses under the weight of questions it has itself raised and simultaneously a new epistemology begins to construct itself. Zimbardo demonstrates that the Restoration marked both the collapse of the Re